Proceedings of the 22nd International Meshing Roundtable 2014
DOI: 10.1007/978-3-319-02335-9_30
|View full text |Cite
|
Sign up to set email alerts
|

Serial and Parallel Mesh Modification Through a Unique Cavity-Based Primitive

Abstract: International audienceA complete mesh generation or mesh adaptation process usually requires a large number of operators : Delaunay insertion, edge-face-element point insertion, edge collapse, point smoothing, face/edge swaps, etc. Independently of the complexity of the geometry, the more operators are involved in a remeshing process, the less robust the process may become. In addition, deriving a parallel version of the process may involve a large number of modifications for each operator. Consequently, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Indeed, if an invalid operation occurs, it is simply rejected. The core of the algorithm uses a unique cavity-based operator [34]. Thus, each meshing operateor is equivalent to a node insertion or reinsertion.…”
Section: Algorithm 2 Mesh Adaptation Loop For Unsteady Flowsmentioning
confidence: 99%
“…Indeed, if an invalid operation occurs, it is simply rejected. The core of the algorithm uses a unique cavity-based operator [34]. Thus, each meshing operateor is equivalent to a node insertion or reinsertion.…”
Section: Algorithm 2 Mesh Adaptation Loop For Unsteady Flowsmentioning
confidence: 99%
“…Many variants of local operator adaptive mechanics are currently employed. [37][38][39][40][41][42][43][44] This has been shown to be unified by the cavity operator, 45 which has yet to be widely implemented but shows promise for producing semi-structured metric-orthogonal regions in the boundary and interior of the domain. 46,47 The di↵erences between a mapped isotropic method and a metric-orthogonal method are shown in Fig.…”
Section: Current Status and Limitations Of Unstructured Grid Adapmentioning
confidence: 99%
“…Michal and Krakos 44 produce metric-conforming grids using only edge split and collapse operations. Loseille and Menier 45 have shown that a cavity based operator unifies these insert, collapse, swap, and node movement operators into a single framework. The flexibility of the cavity operator has enabled metric-orthogonal 46, 47 grid adaptation, which produces grids with locally structured regions and improved dihedral angles.…”
mentioning
confidence: 99%
“…Generating an anisotropic unit mesh H with respect to M requires to use any anisotropic mesh generator [16][17][18][19][20][21]. The results presented in this paper were achieved using our in-house remesher [22]. The general idea is to perform iteratively simple mesh modifications such as vertex insertions/removal, edge swaps/collapses etc., in order to generate unit mesh elements.…”
Section: Generate Meshmentioning
confidence: 99%
“…The general idea is to perform iteratively simple mesh modifications such as vertex insertions/removal, edge swaps/collapses etc., in order to generate unit mesh elements. All the aforementioned operations are performed using a single mesh operator based on cavity remeshing [22].…”
Section: Generate Meshmentioning
confidence: 99%